ANALISIS PENGARUH DISTRIBUSI PENDAPATAN, ANGKA MELEK HURUF PEREMPUAN, SERTA PENGELUARAN PEMERINTAH PADA SEKTOR PENDIDIKAN DAN KESEHATAN TERHADAP VARIASI KESEJAHTERAAN ANAK ANTARPROVINSI DI INDONESIA TAHUN 2010 - Mujiningrum, Dyah; SBM, Nugroho (Diponegoro Journal of Economics, 2013)
This study has three aims. The first aim is to determine variations in the performance of child welfare by the provincial government to give attention to the rights of children by using PPGs (Province Performance Gaps). The second aim is to determine variations in child welfare in each province according to the dimensions of health, education, and protection. The third, to determine the income distribution, female literacy rates, and government expenditure on education and health sectors for the child welfare. The first step on calculate PPGs is derived the expected values for each of the eighteen child-welfare variables using OLS regression analysis. The second step, WINOCENT provides a convenient measure of a multidimensional phenomenon, in this case children’s welfare. The last aim, this study identify income distribution, female literacy rates, and government expenditure on education and health sectors to test for their salience in determining provincial variations in child welfare that were proxied by WINOCENT using OLS regression analysis. The results of the analysis showed, that only the female literacy rate in accordance the theory, this has positive impact and statistically significant on the child welfare.